2018
DOI: 10.4055/cios.2018.10.1.94
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Satellite Ganglion Cysts with Effusion in the Flexor Hallucis Longus Tendon Sheath around the Hallux

Abstract: BackgroundTo describe the clinical and magnetic resonance imaging findings of ganglion cysts with effusion in the flexor hallucis longus tendon sheath around the hallux to evaluate their origin.MethodsPatients with recurrent or painful ganglion cysts around the hallux with effusion in the flexor hallucis longus tendon sheath who underwent surgical treatment at St. Vincent's Hospital from February 2007 to August 2016 were investigated. Surgical indication was a painful or recurrent mass caused by the cystic les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
0
14
1
Order By: Relevance
“…However, we treated a massive effusion in the FHL tendon sheath with stenosing tenosynovitis involving an os trigonum via posterior ankle arthroscopy. This point might be different from reports by Qu et al [19] and Lee et al [20].…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…However, we treated a massive effusion in the FHL tendon sheath with stenosing tenosynovitis involving an os trigonum via posterior ankle arthroscopy. This point might be different from reports by Qu et al [19] and Lee et al [20].…”
Section: Discussioncontrasting
confidence: 92%
“…Qu et al reported cases of diffuse FHL tenosynovitis with effusion at a level proximal to the ankle joint posteriorly and/or between the talar tubercles and the master knot of Henry, although it was treated by open extensive tenosynovectomy [19]. Lee also reported cases of effusion with the FHL tendon sheath at a level of the interphalangeal joint and/or the metatarsophalangeal joint, although it was treated by an open procedure [20]. However, we treated a massive effusion in the FHL tendon sheath with stenosing tenosynovitis involving an os trigonum via posterior ankle arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…The development of a ganglion cyst connected to a tendon sheath is thought to be proceeded by mucoid degeneration of the tendon’s collagen fibers and cellular hyperplasia associated with active mucin secretion. 14 Lee et al 8 suggested that HGC may be secondary to joint injury or repetitive trauma. The hallux is under pressure during weightbearing, and fluid leakage through the stalk (containing the tracts) of the cyst may act as a 1-way valve.…”
Section: Discussionmentioning
confidence: 99%
“…The hallux is under pressure during weightbearing, and fluid leakage through the stalk (containing the tracts) of the cyst may act as a 1-way valve. Lee et al 8 assessed ganglion cysts around the hallux with magnetic resonance imaging and operative detection. It was found that the cysts were connected to synovial cysts in the FHL tendon sheath originating from the interphalangeal or metatarsophalangeal joint.…”
Section: Discussionmentioning
confidence: 99%
“…Intraosseous ganglia contain a gelatinous material with a histopathologic appearance similar to that of a soft-tissue ganglion, and they are rarely reported lesions. They have a tendency to occur in the metaphysis of long bones of the lower extremity, such as distal tibia; however, the wrist, femoral head, medial malleolus, and carpal bones are other well-recognized sites [ 4 , 5 ]. Patients with osseous ganglia experience intermittent pain that frequently increases with activity.…”
Section: Introductionmentioning
confidence: 99%